Fabrication and mechanical behavior of nano-grained LaGdZr2O7 transparent ceramic. Issue 22 (15th November 2021) - Deng, Jirui; Huang, Zhangyi; Wang, Junpu; Tang, Zhe; Liang, Hao; Zhang, Lu; Lu, Tiecheng; Qi, Jianqi; Chen, Bin; He, Duanwei
Abstract: Herein, we report transparent LaGdZr2 O7 nano-grained ceramics with an average grain size of 10 nm prepared using the high-pressure sintering method at 5.0 GPa/450 °C. These ceramics showed improved plastic deformation as compared to transparent micro-grained LaGdZr2 O7 ceramics. Moreover, the fracture toughness of the nano-grained ceramics reached up to 3.4 MPam 1/2, which is 79 % higher than that of the micro-grained samples. This improvement in the fracture toughness of the nano-grained ceramics was associated with the presence of a large number of weak grain boundaries in them.